A constituição imaginária do blockchain : diálogos sobre confiança, descentralização e perspectivas da internet - Seibt, Daniela (2024)
The digital technologies that the advancement of the internet has enabled, especially those based on the ubiquity and mobility of this new information and communication system, have changed the way society organizes and interacts. In the communication industry, with each new tool we are even more surprised by the revolutionary force it can exert on our lives. In this universe of emerging technologies, blockchain is one of the initiatives that has sparked a series of studies in the field of business, and as part of the continuation of the history of the internet, its narrative is challenging old ideas, ways of life and business models. The present study maps the imaginary constitution of blockchain based on the discourse about the technology produced by actors/agents in this area under construction. This research has an exploratory nature, with a qualitative approach and is anchored in a methodological arrangement that includes in-depth interviews and Content Analysis. In the bibliographical survey, we reviewed aspects of communication theories, retraced the history of networks and the internet, looked for authors who highlight propositions about blockchain technology and presented a theoretical outline that retraces the main ideas about the imaginary, the construction of the concept as a technological phenomenon and the dimensions that surround it. Through analysis, we seek to understand the points of convergence between blockchain and communication, from the imaginary, keeping in mind how decentralized solutions can provide more reliable experiences for digital communication in the future.